The Precision Toxicology initiative - Colbourne, John; Chung, Mu-En; Diwan, Gaurav; Singh, Gurdeep; Strähle, Uwe; Russell, Robert B. (Toxicology letters, 2023)
The goal of PrecisionTox is to overcome conceptual barriers to replacing traditional mammalian chemical safety testing by accelerating the discovery of evolutionarily conserved toxicity pathways that are shared by descent among humans and more distantly related animals. An international consortium is systematically testing the toxicological effects of a diverse set of chemicals on a suite of five model species comprising fruit flies, nematodes, water fleas, and embryos of clawed frogs and zebrafish along with human cell lines. Multiple forms of omics and comparative toxicology data are integrated to map the evolutionary origins of biomolecular interactions that are predictive of adverse health effects, to major branches of the animal phylogeny. These conserved elements of adverse outcome pathways (AOPs) and their biomarkers are expected to provide mechanistic insight useful for regulating groups of chemicals based on their shared modes of action. PrecisionTox also aims to quantify risk variation within populations by recognizing susceptibility as a heritable trait that varies with genetic diversity. This initiative incorporates legal experts and collaborates with risk managers to address specific needs within European chemicals legislation, including the uptake of new approach methodologies (NAMs) for setting precise regulatory limits on toxic chemicals.
Online verfügbar: 19. Mai 2023, Artikelversion: 7. Juni 2023
*The PrecisionTox Consortium: John K. Colbourne, Mu-En Chung, Juan Carlos Gonzalez Sanchez, Gaurav D. Diwan, Gurdeep Singh, Uwe Strähle, Robert B. Russell [und viele weitere Personen]
Gesehen am 07.08.2023